Inventory and Financial Performance selected Publicly listed Manufacturing Indonesian and German Companies - S. P.D. Anantadjaya; P. W. Carmelita; S. Juhara; S. Irdiana; I. Moridu; E. Susanti; I. M. Nawangwulan (Финансы: теория и практика)
Inventory management is a fundamental supply chain management phase that affects the country’s economy.The purpose of the study is to determine the effectiveness of inventory management and its impact on the financial performance in the factoring industry, as it has become one of the leading sectors in boosting the development of the national economy.Descriptive and quantitative methods were used, which mainly relied on financial data for 2013–2017 on the selected publicly listed manufacturing companies in Indonesia and Germany based on the LQ45 and DAX stock index, respectively. Several software programs (Microsoft Excel, SPSS, and AMOS) were used for solving the inventory-financial performance and value analysis based on Structural Equation Modeling.The results of the study confirm that inventory performance significantly influences financial performance, as the p-value is below 5%. Inventory performance has an explanatory power of 30.6% for financial performance. An increase in inventory performance will increase financial performance as well. Each indicator has an explanatory power of DSI (101.2%), INVTO (96.4%), FGI (63.3%), WIP (58.3%), and RMI (51.7%) towards inventory performance, which will increase performance as well. For financial performance, each indicator has an explanatory power of ROIC (97.0%); ROE (85.1%); ROA (76.9%); GR (46.7%); PM (5.6%), and OM (5.3%) towards financial performance, which will also contribute to improved efficiency.